2019
DOI: 10.1016/j.immuni.2019.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Natural Genetic Variation Reveals Key Features of Epigenetic and Transcriptional Memory in Virus-Specific CD8 T Cells

Abstract: Highlights d Genetic variation in evolutionarily distant mice regulates gene expression in cis d Distinct TF families mediate stable and transient chromatinlevel responses d T-box and Runx family TFs cooperate in stable chromatin remodeling in CD8 T cells d Stability is associated with congruent remodeling of neighboring chromatin sites

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 82 publications
6
47
0
Order By: Relevance
“…For example, this model may be useful in interrogating additional mechanisms by which these cohabiting, inbred mice respond differently to therapeutic interventions in tumors. Studies suggest that even though inbred mouse strains were created to be essentially genetically identical, these mice are made through many generations of brother-sister mating, and minor variations can arise over time that could create differences in the host immune responses (68,69). Performing whole genome sequencing in this model could be useful for addressing the contributions of minor genetic variations to the responder versus nonresponder phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…For example, this model may be useful in interrogating additional mechanisms by which these cohabiting, inbred mice respond differently to therapeutic interventions in tumors. Studies suggest that even though inbred mouse strains were created to be essentially genetically identical, these mice are made through many generations of brother-sister mating, and minor variations can arise over time that could create differences in the host immune responses (68,69). Performing whole genome sequencing in this model could be useful for addressing the contributions of minor genetic variations to the responder versus nonresponder phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…From a more general perspective, the intimate link between T-bet and chromatin modifications is underlined by a recent study exploring chromatin and gene expression changes associated with viral infection in mouse CD8 T cells. The authors reported that T-box and Runx genes have been shown to act as critical mediators of chromatin remodeling during CD8 T cell activation (27).…”
Section: T-bet-ifn-γ Pathwaymentioning
confidence: 99%
“…Van der Veeken et al. linked genetic variation to allelic imbalances in chromatin accessibility to reveal the contribution of specific TF DNA-binding motifs to stable and transient gene regulation in CD8 T cells responding to acute viral infection [ 89 ]. They identified some stably responsive DNA elements that were characterised by chromatin remodelling events affecting different neighbouring sites and requiring distinct TF-binding motifs for their co-operations in virus-specific CD8 T cells.…”
Section: Do Enhancer Snps Influence the Inflammatory Response In Diabmentioning
confidence: 99%
“…They identified some stably responsive DNA elements that were characterised by chromatin remodelling events affecting different neighbouring sites and requiring distinct TF-binding motifs for their co-operations in virus-specific CD8 T cells. Interestingly, transiently regulated regions had a higher degree of constitutive accessibility than stably regulated peaks, and relatively minor changes were induced by activation [ 89 ]. As discussed previously, important chromatin remodelling events are associated with stability across several cell types and experimental systems.…”
Section: Do Enhancer Snps Influence the Inflammatory Response In Diabmentioning
confidence: 99%
See 1 more Smart Citation